A KAP study on water, sanitation and hygiene among residents of Parla village, Kurnool district, Andhra Pradesh - Hothur, Rekha; Arepalli, Sreedevi; Doddoju Veera Bhadreshwara, Anusha (International Journal Of Community Medicine And Public Health, 2019)
Background: Ensuring access to safe drinking water and sanitation for rural people is the key catalyst for economic and human growth. However extreme poverty inhibits a significant portion of rural population from getting access to sanitation facilities and safe drinking water services. The study was conducted to assess knowledge, attitudes and Practices (KAP) with regard to water, sanitation and hygienic practices and to identify the socio-demographic factors in relation. Methods: A cross-sectional study sample comprising of 236 households was conducted in the rural field practice area after obtaining Institutional Ethics Committee approval. Proportionate sample of 20% households were taken from each ward and houses were selected by systematic random sampling method. Knowledge, attitude and practices regarding water, sanitation and hygiene were assessed using pretested semi-structured questionnaire. Results: Out of 236 households majority interviewed were females 169 (71.6%), illiterate (54.2%) and unskilled workers 122 (51.7%) belonging to class V socio-economic status 165 (69.9%). Household lavatory is absent in 114 (48.3%) households. Out of 122 (51.7%) households having sanitary lavatories only 59 (48.4%) were fully utilizing them remaining 63 (51.6%) households were going to open defecation even though sanitary lavatory was present. A significant association between defecation practice and socio-economic status, education were observed. Conclusions: This study shows that even though they have sufficient knowledge on water purification, Sanitation and hygiene this was not translated into practice because of poor attitude.